Determinants of industry concentration and dispersion - Jamison, Mark A.,Tęcza, Jakub (American Enterprise Institute, 2024)
Given the political and public interest in rising industry concentration in developed economies, researchers have been working on uncovering underlying mechanisms and implications. Various causes of concentration have been proposed, although rarely tested in a comprehensive model. We study five distinct phenomena and their association with industry concentration: 1) Industry regulation, 2) mergers, 3) information technology use, 4) imports, and 5) productivity. We find that greater concentration within an industry is related to higher productivity, more regulation, and more merger activity. On the other hand, it is lower with more imports and seemingly unrelated to the extent of information technology use. The most economically significant relationship is between concentration and industry productivity.
https://www.aei.org/research-products/working-paper/determinants-of-industry-concentration-and-dispersion/
Keywords: Graue Literatur; Industry concentration; regulation; information technology; mergers